Penggunaan Buku Tegak Bersambung untuk Meningkatkan Gaya Tulis Siswa pada Kelas III Di Sekolah Dasar Negeri Rangda Malingkung 1 - Shapiyah Nayla; Arifin Riadi (Yayasan Arrahman Nahdlatul Wathan, 2026)
Handwriting is a fundamental skill that supports elementary school students' written communication; however, many third-grade students still experience difficulties in producing neat, proportional, and legible handwriting. This study aimed to improve the handwriting style of third-grade students through the use of the Buku Tegak Bersambung at SD Negeri Rangda Malingkung 1. The research employed Classroom Action Research (CAR) using the Kemmis and McTaggart model, consisting of two cycles involving planning, action, observation, and reflection. The participants were 16 third-grade students. Data were collected through observation, handwriting performance tests, questionnaires, and documentation, and analyzed using qualitative and quantitative descriptive techniques. The findings revealed that the implementation of the Buku Tegak Bersambung effectively improved students' handwriting skills, as indicated by the increase in the average score from 80.94 in Cycle I to 94.06 in Cycle II, with classical learning mastery reaching 100%. Moreover, students demonstrated highly positive responses to the learning media, with an average response rate of 99.2%. These findings indicate that the Buku Tegak Bersambung is an effective instructional medium for improving the handwriting skills of third-grade elementary school students.